The Mongol Art of War : Chinggis Khan and the Mongol Military System - May, Timothy (South Yorkshire Pen and Sword, 2007)
Overturns myths and misunderstandings that distort the understanding of Mongol warfare, and demonstrates that the armies of Chinggis Khan had more in common with modern ones than with the armies of ancient Rome.
Include Illustrations and Index
Keywords: Military leadership. -- Mongolia -- History -- To 1500. -- Military art and science -- Genghis Khan